(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
TB is a leading cause of morbidity and mortality worldwide. However, public health services globally reported only 66% of the estimated TB cases in 2014. Moreover, less than 5% of notified TB cases were tested for drug resistance capacity and an over reliance on chest radiography and/or sputum smear microscopy as diagnostic tools. The relying on conventional culture and drug susceptibility testing (DST). Detecting more cases, detecting them early and rapidly identifying drug resistance are essential for improving individual patient health and avoiding transmission resents a paradigm shift in the diagnosis of TB and drug-resistant TB by simultaneously detecting Mycobacterium tuberculosis and Rifampicin resistance-conferring mutations in a closed system suitable for use outside conventional laboratory settings in less than 2 hours, directly from sputum samples. Objective: To find out the challenges in diagnosis of TB and MDR TB by Gene-Xpert in Bangladesh Methodology; Both quantitative and qualitative methods study designs were used. All the 43 Centres in Bangladesh where the Gene X pert test are carried out were included. In addition selective officials/staff from national and sub-national level were included as respondents for focus group discussion (FGD) and in-depth interview. Verbal informed consent was obtained from participants before starting interviews. Analysis of data was done using SPSS software program. Results: Xpert MTB/RIF was first introduced in Bangladesh in March 2012. Till December 2015, a total of 61 Xpert MTB/ RIF machines were functioning at 43 sites in the country. In 42 sites the GeneXpert machines are placed in a separate room and in one site it is placed along with other general pathological laboratory activities. It was found that in all sites necessary physical support like air-cooler, dust control, UPS as well as regular electricity and water supply were available. Out of 43 sites, 38 have 4-module and 5 sites have 16-module machine. In totall, 55 four module machines and 6 sixteen module have been established. Out of these only one 4modul machine was non-functioning. In about half (48.8%) of the sites machines are run twice a day and in 17 sites (39.5%) only once while in 5 sites (NGO supported sites) machines are run 3 times a day. In 19 (44.2%) sites 1-4 samples are tested per day and in 16(37.2%) sites 5-8 samples/day. Per day 9-20 samples are tested in 4(9.3%) centres while in other 4 centres 21-30 samples are tested daily. In all the centres a total of about 300 samples are tested in a single working day. In total, 38 sites informed about problems they faced in operating the machine. The most common problem was module failure (67.4%), followed by delay in maintenance support (46. 5%). Inadequate cartridge supply and load shading were faced by 16.3% and 11.6% respectively. In 42 sites there were needs for support. The most common support they need is refresher training (93%), followed by maintenance training by 79.1%, and Software training by 18.6%. The responses from both FDG and in-depth interviews were as follows: Most common problem faced by the heath workers were lack of timely maintenance of Machines, false result of Rifampacin Resistance due to low bacterial load, module failure, no proper sputum transport mechanism, lack of appropriate centrifuge machine for processing of samples of EP cases and inadequate man power. From the past experience the group provided some valuable suggestions and comments as follows; A well maintained sputum transportation mechanism to be established. Stable power supply is absolutely necessary as discontinuation of electricity even for a fraction of second will cause erroneous test result. More machines need to made available for easier access. Machine operator needs refresher training including training related to day- today maintenance and software system. Good quality sample in suffi cient amount to be ensured for Xpert testing to produce accurate results. Conclusion: Gene-Xpert machine is very useful in diagnosis of MDR and Rifampacin Resistance M. tuberculosis. Module failure is a common problem and their replacement takes longer time. Frequent errors are shown that might be due to poor quality of sample, unstable electricity supply or poor skill of machine operators. Proper training of operators and proper sputum transport system is urgently needed for efficient use of these machines. SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, Vol. 14, No. 2, 2017, Page: 1-11